Pressure to Plagiarize and the Choice to Cheat: Toward a Pragmatic Reframing of the Ethics of Academic Integrity - Alicia McIntire; Isaac Calvert; Jessica Ashcraft (MDPI AG, 2024)
In light of the burgeoning influence of LLM AI programs like ChatGPT in a variety of academic contexts and the COVID-19 pandemic's expansion of virtual classrooms and coursework, the philosophical framing of academic integrity and plagiarism is being re-examined. In concert with these technological changes, students are also facing increasing pressure to succeed in their academic pursuits. Inasmuch as the consequences of failure in these contexts are often dire academically, socially, and financially, we argue that students often weigh the choice to plagiarize not as an ethical issue but as a pragmatic mitigation of risk. Using three salient examples of plagiarism and cheating from higher education in North America as case studies, we explore the pressures and contexts that have influenced the choice to engage in plagiarism and cheating through this pragmatic lens. As an ethical framing of the issue of academic integrity has been less effective in ameliorating plagiarism in this pressurized climate, we propose a way in which educators, administrators and policy makers might approach the issue in this same pragmatic frame. In short, rather than combat plagiarism by teaching its moral repugnance, we propose educators could argue instead that plagiarism and cheating are pragmatically untenable simply because they are detrimental to learning.